Banana Fusarium wilt (Fusarium oxysporum f. sp. cubense) control and resistance, in the context of developing wilt-resistant bananas within sustainable production systems - Siamak, S.B.; Zheng, S. (Elsevier, 2018)
Banana (Musa spp.) is seriously threatened by the soil-borne fungus Fusarium oxysporum f. sp. cubense (Foc), also known as Panama disease. Attempts to control Fusarium wilt with fungicides damage soil health and have limited efficiency due to pathogenic variability. Elucidating the mechanism of infection and molecular basis of host defense through banana genome sequencing, genome editing and proteomic profile analysis will help formulate strategies to develop resistant cultivars. This will include research to better understand the functions of Fusarium wilt-resistance proteins. Transgenic approaches and protoplast fusion could be employed as tools for transferring resistance genes from wild relatives to commercial banana varieties, and may serve as a new strategy in solving the problems faced by banana breeding programmes. Evaluation of banana germplasm for resistance to Fusarium wilt using in vitro mutation and selection, along with somaclonal variation and somatic hybridization, could improve banana breeding efficiency for resistance against Foc. Plant hormones could also play an important role in regulating plant growth and defense by mediating developmental processes and signaling networks involved in banana responses to Foc. A complementary approach for managing Fusarium wilt, such as exclusion, surveillance and biological control as important components of integrated disease management programs must be considered to prevent and contain contagion. This includes studies on banana plant-microbe interactions, embracing both plant growth promoting rhizobacteria (PGPR) to induce Foc resistance, and exploring Foc-derived elicitors for inducing defense-related enzymes in bananas. The role of Silicon and crop and livestock integration must also be included in the Fusarium control toolbox. The current review also gathers knowledge of the biotechnological approaches along with biological control of Fusarium wilt of banana that will provide researchers insights and criteria to develop future studies.